Effect of Social Skill Training on Anxiety and Performance of High School Students: Assessing the efficacy of low threshold education services for enhancing mental wellbeing in high school students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Adolescence is a time of heightened stress sensitivity that puts teens at greater risk for mental health issues such as burnout, depression, anxiety and externalization. This malfunctioning growth can be avoided by early detection with psychological and low-level services to resolve these needs. Schools should offer an essential atmosphere for social needs to be recognized and discussed. The intent of this report is to explain the creation of a study aimed at assessing the efficacy of low threshold education services that promote young people's mental wellbeing and testing moderators of the efficacy of services.